2018
DOI: 10.1038/s41598-018-19310-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-145-5p and microRNA-320a encapsulated in endothelial microparticles contribute to the progression of vasculitis in acute Kawasaki Disease

Abstract: Kawasaki Disease (KD) is an acute inflammatory disease that takes the form of systemic vasculitis.Endothelial microparticles (EMPs) have been recognized as an important transcellular delivery system. We hypothesized whether EMPs are involved in vasculitis in acute KD. Fifty patients with acute KD were enrolled, divided into two subgroups: those with coronary artery lesions (CAL) (n = 5) and those without CAL (NCAL) (n = 45). EMPs were measured using flow cytometry, and microRNA (miR) expression profiling was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…We found that the expression of HMGB1/sRAGE/ NF-κB increased in the acute phase of KD. Notably, in the acute phase of KD, the CAL group exhibited higher levels than the NCAL group, as regards these three indicators [30]. Furthermore, we established a rabbit model of KD.…”
Section: Discussionmentioning
confidence: 96%
“…We found that the expression of HMGB1/sRAGE/ NF-κB increased in the acute phase of KD. Notably, in the acute phase of KD, the CAL group exhibited higher levels than the NCAL group, as regards these three indicators [30]. Furthermore, we established a rabbit model of KD.…”
Section: Discussionmentioning
confidence: 96%
“…199 Consistent with whole blood samples, plasma miR-145-5p levels are highly expressed in from patients with KD. 200 Plasma miR-125a-5p levels are also significantly elevated in both of acute and convalescent KD patients compared with controls, suggesting that miR-125a-5p may be potential diagnostic biomarkers for early KD. 201 In the recent study, miR-186 is confirmed to be significantly up-regulated in the serum of patients with KD and in HUVECs stimulated with KD serum, and its serum expression is down-regulated to normal levels in convalescent KD.…”
Section: Kawasaki Diseasementioning
confidence: 95%
“…Collectively, the studies discussed in this section lead to the conclusion that EMVs have the ability to activate both endothelium and leukocytes, which fortifies migration of leukocytes to the site of inflammation. Recently, Nakaoka et al (154) have put forward important and thought-provoking observations on the proinflammatory mechanism of EMV. First, two unique microRNAs (hsa-miR-145-5p and hsa-miR-320a) were encapsulated in EMVs.…”
Section: Endothelial-derived Microvesicles (Emvs) and Inflammationmentioning
confidence: 99%